(untitled) (Journal of Agriculture and Environment, 2015)
The study was designed to determine the profitability and resource use efficiency of buckwheat production in Chitwan. The study used 42 buckwheat growers from 300 farmers adopting different pollinator friendly practices. Descriptive and statistical tools including Cobb-Douglas production function were used on data collected from structured interview schedule to accomplish the objectives. The benefit cost ratio (1.25) indicates that buckwheat production was profitable. The magnitude of regression coefficients of buckwheat implied that use of tractor and nutrient cost had significant positive effects on gross return. According to estimated allocative efficiency indices, it is suggested to reduce labor and seed cost by about 148% and 143%, respectively and; increase the use of tractor and nutrient inputs by about 63% and 19%, respectively. Extension of modern technologies with adjustment on resource use explains for increase in return and profit from buckwheat production which indirectly promotes and ensure forage for pollinators in study area.